Antiphospholipid Antibodies and Infection: Non Nova Sed Nove - Sciascia, Savino; Radin, Massimo; Bazzan, Mario; Montaruli, Barbara; Cosseddu, Domenico; Norbiato, Claudio; Bertero, Maria Tiziana; Carignola, Renato; Bacco, Beatrice; Gallo Cassarino, Silvia; Roccatello, Dario (Frontiers in Immunology, 2021)
The clinical significance of antiphospholipid antibodies (aPL) in the context of infections has attracted attention since their first discovery in patients with syphilis. In fact, the recognition of aPL in patients with infections has been described in parallel to the understating of the syndrome. Since the first description of aPL positive tests in three patientswith Covid-19 diagnosed in January 2020 in Wuhan, China, a large number of studies took part in the ongoing debate on SARS-2-Cov 2 induced coagulopathy, and many following reports speculated a potential role for aPL. In order to get further insights on the effective role of detectable aPL in the pro-thrombotic status observed in COVID-19 patients, we performed an observational age-sex controlled study to compare the aPL profile of hospitalized patients with COVID with those observed in a) patients with thrombotic APS and b) patients with cultural/serologically-proved infections. Our data showed positive aPL testing in about half of the patients (53%) with COVID-19 and patients with other viral/bacterial infections (49%). However, aPL profile was different when comparing patients with overt APS and patients with aPL detected in the contest of infections. Caution is therefore required in the interpretation and generalization of the role of aPL s in the management of patients with COVID-19. Before introducing aPL testing as a part of the routine testing in patients with COVID-19, larger well-designed clinical studies are required. While the pro-thrombotic status in patients with COVID-19 is now unquestionable, different mechanisms other than aPL should be further investigated.